Human mitochondrial ferritin exhibits highly unusual iron-O2 chemistry distinct from that of cytosolic ferritins - Justin M. Bradley; Zinnia Bugg; Jacob Pullin; Geoffrey R. Moore; Dimitri A. Svistunenko; Nick E. Le Brun (Nature Communications)
Abstract Ferritins are ubiquitous proteins that function in iron storage/detoxification by catalyzing the oxidation of Fe2+ ions and solubilizing the resulting Fe3+-oxo mineral. Mammalian tissues that are metabolically highly active contain, in addition to the widespread cytosolic ferritin, a ferritin that is localized to mitochondria. Mitochondrial ferritin (FtMt) protects against oxidative stress and is found at higher levels in diseases associated with abnormal iron accumulation, including Alzheimer’s and Parkinson’s. Here we demonstrate that, despite 80% sequence identity with cytosolic human H-chain ferritin, Fe2+ oxidation at the catalytic diiron ferroxidase center of FtMt proceeds via a distinct mechanism. This involves a mixed-valent ferroxidase center (MVFC) that is readily detected under the O2-limiting conditions typical of mitochondria, and formation of a radical on a strictly conserved Tyr residue (Tyr34) that is key for the activation of O2 and stability of the MVFC. The possible origin of the mechanistic differences exhibited by the highly-related human mitochondrial and cytosolic H-chain ferritins is explored.